A verticalização da Vila Romana: 1964 à 2012 - Michelin, Rodrigo Fernandes (2012)
This dissertation presents the vertical growth of Vila Romana neighborhood, city of Sao Paulo. The research provides a list of residential buildings and makes an analytical description of different types of condos that has been changing the whole area from 1964 until 2011. The research points the increasing urban segregation derived from large gated communities that have settled in Vila Romana caused from the new guidelines for land use and occupation established in 2004. The work not only presents the evolution of housing, but also the city regression by the decreasing of city's public spaces.